Balance of payments, exchange rates, and competitiveness in transition economies - Bléjer, Mario I.; Skreb, Marko (Boston : Kluwer Academic Publishers, 1999)
This book is a collection of studies dealing with the different issues related to the liberalization of external relations in economies moving from a socialist to a market-based system.
Includes bibliographical references and index.
osc 24/10/17
Loans
Keywords: Monetary policy; Economic stabilization; Balance of payments; Competition, International; Foreign exchange rates--Government policy; International economic relations; Economics